Body Composition, Biological Maturation, and Socioeconomic Status of Young Talented Female Swimmers and Gymnasts - Bernink, M. J. E; Erich, W. B. M.; Peltenburg, A. L.; Zonderland, M. L.; Huisveld, I. A. (Biomechanics and Medicine in Swimming, 1983)
In recent years attention has been given to the effects of sport activities at younger ages on growth, body composition, and biological maturation. Female swimmers seem to be slightly taller than the average population but only after the age of 12 (Andrew et al., 1972). Eriksson et al. (1978) found in a longitudinal study that female swimmers grew only an average of 4 cm in height between ages 13 and 21 years. However, female gymnasts seem to be smaller and have less fat than control females (Erich, 1980; Panzkova, 1977). Biological maturation seems to be delayed in female gymnasts but not in female swimmers (Marker, 1979; Malina et al., 1978). Growth and biological maturation are influenced by genetic and environmental factors such as nutrition and socioeconomic status (Eveleth and Tanner, 1976). Children from parents with a high socioeconomic status are taller and mature earlier. This was also true in the Netherlands in 1965 (van Wieringen, 1972). However, in some highly developed countries (e.g., Sweden) the socioeconomic status no longer seems to be correlated with growth and biological maturation (Furu, 1976; Lindgren, 1976). The purpose of this study was to investigate whether differences in height, body composition, and biological maturation in young female athletes, swimmers and gymnasts can be explained by differences in socioeconomic status.